“It is what it is”: an ethnography of women's experience of drought in Madziva, Zimbabwe - Kanengoni, Mistancia (Social Anthropology, 2020)
Bad weather conditions such as drought have had detrimental effects on the agrarian life of the people in Madziva rural area, Zimbabwe. Due to the unfavorable weather conditions in this area, poverty and unemployment, most men migrated and continue to migrate to the urban areas in search of greener pastures. This research focuses on how these more frequent extreme weather conditions in Madziva, resulting in less predictable seasons, have increased incidences of precarity. This is important as it portrays how the climate has changed, its effect and the anxiety and expectations around it. Furthermore, providing perception of the nature of climate change in the village is important in order to assess the evidence of nature and level of climate change (manifesting through drought). As a result of the uncertainty caused by drought, the migration of men had been rampant in Madziva, and thus the village is characterized by a significant number of female-led households. To understand the social, political and economic dynamics of what it means to survive in a time of drought for ‘fragmented' families, an ethnographic research was conducted in Madziva over two months (14 June 2017 to 15 July 2017) and (10 December 2017 to 11 January 2018) during one of the worst droughts in Zimbabwe. This research follows the everyday lives of eight women and the interactions with 15 more women through focus group interviews in order to understand the strategies used to achieve survival. In this thesis, the results of an ethnography of women's experience of drought particularly in Madziva rural area in Zimbabwe between June 2017 and mid-January to mid-February 2018 are presented. It further explores, the locals' understandings of extreme weather conditions particularly in Madziva rural area and how practices, particularly those linked to gender, are shaped or reinforced. This research found out that the people of Madziva rural area, particularly women are severely affected by drought as compared to men. This is because of the expectations of managing the household and caring for children which requires them to be heavily reliant on natural resources. The reliance on natural resources has been due to the very poor and non-performing Zimbabwean economy, however, these are the resources which become scarce in a time of drought, which exacerbates precarity. Additionally, women in rural areas such as Madziva have less access to critical information on shifts in cropping patterns and weather alerts, and this can be linked to the gendered structure of the village, where men are seen as the principle holders of knowledge of the land. Furthermore, women also have very little power in decision making and access to resources because of the land ownership titles often given to the men of the household. However, with iv the high migration to urban centers, there is a gap that the women of Madziva must navigate and this thesis aims to explore how this occurs. For instance, during the fieldwork, it became evident that irrespective of all these challenges that are caused by drought, women are always expected to make a plan to provide for their families although there is a stiff competition for the remaining natural resources. Women in Madziva negotiated relationships of marginality, responsibility, togetherness and belonging through the ways they experienced the challenges ushered by drought.